2020
DOI: 10.3389/fncel.2020.521199
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Motor KIF3B Acts as a Key Regulator of Dendritic Architecture in Cortical Neurons

Abstract: Neurons require a well-coordinated intercellular transport system to maintain their normal cellular function and morphology. The kinesin family of proteins (KIFs) fills this role by regulating the transport of a diverse array of cargos in post-mitotic cells. On the other hand, in mitotic cells, KIFs facilitate the fidelity of the cellular division machinery. Though certain mitotic KIFs function in post-mitotic neurons, little is known about them. We studied the role of a mitotic KIF (KIF3B) in neuronal archite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…To assess whether deficits in memory due to KIF3B depletion can be attributed to a structural change in prelimbic neurons, we next carried out dendritic imaging analysis in the prelimbic cortex. Previous studies have shown that KIF3B plays a role in the structural morphology of neurons [ 30 , 38 ], and work from our lab has found that KIF3B knockdown in cortical neurons causes an increase in dendritic arborization [ 30 ]. We have also found that KIF3B depletion increases the number of mushroom and thin spines [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To assess whether deficits in memory due to KIF3B depletion can be attributed to a structural change in prelimbic neurons, we next carried out dendritic imaging analysis in the prelimbic cortex. Previous studies have shown that KIF3B plays a role in the structural morphology of neurons [ 30 , 38 ], and work from our lab has found that KIF3B knockdown in cortical neurons causes an increase in dendritic arborization [ 30 ]. We have also found that KIF3B depletion increases the number of mushroom and thin spines [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that KIF3B plays a role in the structural morphology of neurons [ 30 , 38 ], and work from our lab has found that KIF3B knockdown in cortical neurons causes an increase in dendritic arborization [ 30 ]. We have also found that KIF3B depletion increases the number of mushroom and thin spines [ 30 ]. Alsabban et al found a similar increase in mushroom spines of dissociated hippocampal neurons from KIF3B mutant mice [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…KIF3B also has a dendritic phenotype. Post-developmental knockdown of KIF3B in dissociated cortical neurons showed that the overall density of dendritic spines was increased [ 56 ]. This corresponded with an increase in both mushroom and thin spines [ 56 ].…”
Section: Structural Plasticitymentioning
confidence: 99%
“…Post-developmental knockdown of KIF3B in dissociated cortical neurons showed that the overall density of dendritic spines was increased [ 56 ]. This corresponded with an increase in both mushroom and thin spines [ 56 ]. Dendritic branching and growth are mediated by microtubule polymerization [ 57 ].…”
Section: Structural Plasticitymentioning
confidence: 99%